2011
DOI: 10.1002/cbdv.201000290
|View full text |Cite
|
Sign up to set email alerts
|

Glandular Trichomes and Essential Oil Composition of Endemic Sideritis italica (Mill.) Greuter et Burdet from Central Italy

Abstract: Sideritis italica (Mill.) Greuter et Burdet belongs to the Lamiaceae family and is endemic to Italy. The glandular trichomes (morphology, distribution, histochemistry, and ultrastructure) of the plant were studied for the first time, along with the chemical composition of the essential oils. Abundant non-glandular hairs and peltate (type A) and capitate (types B, C(1), and C(x)) glandular trichomes were observed both on the vegetative and reproductive organs. The histochemical procedures and the ultrastructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Differently, in Ln terpenoids were scarce (25.7%), while fatty acids and esters (32.2%) and phenols (13.4%) were present in major percentages. The composition of the investigated samples differed greatly from the results reported earlier for other species of Sideritis, which generally contain essential oils rich in monoterpene hydrocarbons such as α-pinene, β-pinene, sabinene, myrcene, and limonene, or, to a lesser extent, in sesquiterpene hydrocarbons such as δ-cadinene and β-caryophyllene [4,13]. The quantitative prevalence of diterpenoids in Lb and Lm is worth mentioning as they do not appear very often in the essential oil of Sideritis species because of their low volatility.…”
contrasting
confidence: 79%
See 1 more Smart Citation
“…Differently, in Ln terpenoids were scarce (25.7%), while fatty acids and esters (32.2%) and phenols (13.4%) were present in major percentages. The composition of the investigated samples differed greatly from the results reported earlier for other species of Sideritis, which generally contain essential oils rich in monoterpene hydrocarbons such as α-pinene, β-pinene, sabinene, myrcene, and limonene, or, to a lesser extent, in sesquiterpene hydrocarbons such as δ-cadinene and β-caryophyllene [4,13]. The quantitative prevalence of diterpenoids in Lb and Lm is worth mentioning as they do not appear very often in the essential oil of Sideritis species because of their low volatility.…”
contrasting
confidence: 79%
“…In fact, only five species of this genus, S. hirsuta from Spain [4], S. italica from Sicily (South Italy) [6] and Camerino (Central Italy) [13], S. perfoliata and S. dichotoma from Turkey [12] and S. scardica from Bulgaria [14] have been previously described to present diterpenes as major or particularly abundant constituents. Different phytochemical studies have revealed that ent-kaurene type diterpenoids are the most frequently found in Sideritis species, particularly those growing in the Eastern Mediterranean Basin [3], and sideridiol in particular has been already isolated from the acetone extract of S. libanotica ssp.…”
mentioning
confidence: 99%
“…According to Giuliani et al (2011), S. italica is described in the Flora italica" as S. syriaca [40]. Comparing the fingerprints of both species (▶ Fig.…”
Section: Resultsmentioning
confidence: 99%